Translation Methods of Economic Neologisms in Internet Discourse - Irgasheva Shokhida Sadriddinovna (Journal of Business Economics and Agribusiness, 2025)
This study examines the methods used to translate economic neologisms in internet discourse into Uzbek, focusing on their adaptation in professional and academic settings. The research aims to identify the most effective translation strategies, including loan translation, semantic expansion, and hybrid adaptation, while considering linguistic and cultural factors. The study employs a qualitative descriptive method, analyzing various economic neologisms and their translation techniques based on existing translation theories. Data is collected from English-language internet sources and compared with their Uzbek equivalents to evaluate translation accuracy and contextual appropriateness. The findings reveal that loan translation and naturalization are the most commonly used methods, allowing for better comprehension among Uzbek speakers while preserving the original term's meaning. However, in cases where direct equivalents do not exist, functional and descriptive equivalents are applied to maintain clarity. The study highlights the challenges in translating rapidly emerging economic terminology and suggests a structured approach to developing standardized economic terms in Uzbek